Clinical epidemiological characterization and survival in patients under 19 years with leukemia - Nodalys Querol Betancourt; Margarita Isabel Chávez Isla; Coralia Cristina Leblanch Fernández; Niurbis Jimenez Portuondo (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Leukemia is the most frequent cancer in childhood and represents 41 % of all the malignancies in children under 15 years.   Objective: To describe the clinical epidemiological characteristics and survival in children and adolescents with leukemia.  Method:  A descriptive, longitudinal and retrospective study of 82 patients under 19 years, with diagnosis of leukemia was carried out. They were assisted in the Regional Service of Hematology at Dr. Antonio María Béguez César Teaching Southern Children Hospital in Santiago de Cuba, from January, 2014 to December, 2018.   Results: In the case material there was a  prevalence of the 1-4 age group (42.7 %), male sex (59.7 %), mixed race children (48.8 %), acute lymphoid leukemia as morphological variant (73.2 %), as well as the anemic and fever syndrome (97.7 and 86.6 %, respectively).  Complete remission was achieved in 89.0 % of the patients after concluding the first phase of the treatment and 17.1 % presented some type of relapse during their clinical course, where the most affected site was the bone marrow. A global survival of 67.1 % was achieved.   Conclusions: The results of the study are encouraging and do not differ from the world clinical and epidemiological context, taking into account  the non availability of diagnosis means in the province, with advanced technology, for a better stratification of patients.